2016
DOI: 10.1155/2016/1910694
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Safety and Effectiveness of Intense Pulsed Light in the Treatment of Meibomian Gland Dysfunction

Abstract: Purpose. This study aims to explore the safety and efficacy of a novel treatment-intense pulsed light (IPL) in MGD eyes. Methods. This study is a prospective and open label study. Forty eyes of 40 MGD patients were recruited in the study and received 4 consecutive IPL treatments on day 1, day 15, day 45, and day 75. Ten ocular surface symptoms were evaluated with a subjective face score at every visit. Best spectacle corrected visual acuity, intraocular pressure (IOP), conjunctival injection, upper and lower t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
86
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(118 citation statements)
references
References 42 publications
18
86
2
1
Order By: Relevance
“…Our results are in agreement with several trials, which have demonstrated the efficacy of IPL for the treatment of MGD 1317. The mechanism of action is, however, not known.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are in agreement with several trials, which have demonstrated the efficacy of IPL for the treatment of MGD 1317. The mechanism of action is, however, not known.…”
Section: Discussionsupporting
confidence: 93%
“…The first suggestion that IPL might improve MGD came from Toyos, who observed that rosacea subjects treated with IPL reported an improvement in their DED symptoms 12. Since then, several studies have shown that IPL therapy has a beneficial effect on MGD in patients with and without rosacea 1317…”
Section: Introductionmentioning
confidence: 99%
“…The device and the nature of the light it emits have been reviewed . Following reports that serial periocular intense pulsed light treatments improve signs and symptoms of dry eyes in individuals with acne rosacea and ocular surface disease, the clinical application of intense pulsed light devices have been extended to include the treatment of MGD …”
mentioning
confidence: 99%
“…The emerging clinical data regarding the safety and efficacy of intense pulsed light treatment for MGD suggests that a series of two or more intense pulsed light treatments can improve symptoms, tear film characteristics, including tear film break‐up time and clinical signs of MGD; however clinical guidelines regarding candidate selection, the number and frequency of treatments and the efficacy of post‐intense pulsed light meibomian gland expression (MGX) are yet to be established. At the time of writing, of the five published studies assessing the efficacy of intense pulsed light as a treatment for MGD, three were retrospective reviews of treatment series involving individuals with moderate to advanced MGD treated with the Quadra Q4 (DermaMed Solutions, LLC, Lenni, Pennsylvania, USA) intense pulsed light system using a proprietary ‘dry eye mode’ setting.…”
mentioning
confidence: 99%
“…A total of 5 μ l of 2% sodium fluorescein was instilled into the inferior conjunctival cul‐de‐sac of both eyes of each subject using a micropipette, without touching the ocular or the lid surface by the micropipette (Jiang et al. ). The subject was asked to blink naturally without squeezing three to five times to ensure proper mixing of the fluorescein dye throughout the tear film.…”
Section: Methodsmentioning
confidence: 99%